Progressive brain metabolic changes under deep brain stimulation of subthalamic nucleus in parkinsonian rats. (12th February 2015) - Melon, Christophe; Chassain, Carine; Bielicki, Guy; Renou, Jean‐Pierre; Kerkerian‐Le Goff, Lydia; Salin, Pascal; Durif, Franck
Abstract Deep brain stimulation (DBS) of the subthalamic nucleus (STN) is an efficient neurosurgical treatment for advanced Parkinson's disease. Non‐invasive metabolic neuroimaging during the course of DBS in animal models may contribute to our understanding of its action mechanisms. Here, DBS was adapted to in vivo proton magnetic resonance spectroscopy at 11.7 T in the rat to follow metabolic changes in main basal ganglia structures, the striatum, and the substantia nigra pars reticulata (SNr). Measurements were repeated OFF and ON acute and subchronic (7 days) STN‐DBS in control and parkinsonian (6‐hydroxydopamine lesion) conditions. Acute DBS reversed the increases in glutamate, glutamine, and GABA levels induced by the dopamine lesion in the striatum but not in the SNr. Subchronic DBS normalized GABA in both the striatum and SNr, and glutamate in the striatum. Taurine levels were markedly decreased under subchronic DBS in the striatum and SNr in both lesioned and unlesioned rats. Microdialysis in the striatum further showed that extracellular taurine was increased. These data reveal that STN‐DBS has duration‐dependent metabolic effects in the basal ganglia, consistent with development of adaptive mechanisms. In addition to counteracting defects induced by the dopamine lesion, prolonged DBS has proper effects independent of the pathological condition. <boxed-text content-type="graphic" id="jnc13015-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> Non‐invasive metabolic neuroimaging might be useful to understand the physiological mechanisms of deep brain stimulation (DBS). Here, we demonstrate the feasibility of repeated high‐field proton magnetic resonance spectroscopy of basal ganglia structures under subthalamic nucleus DBS in control and parkinsonian rats. Results show that DBS has both rapid and delayed effects either dependent or independent of disease state.